PENGARUH MAKASSAR PADA PENAMAAN KAMPUNG DAENGAN DAN BUGISAN DI KERATON YOGYAKARTA - Yustina Hastrini Nurwanti (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2018)
The toponym of the kampongs Daengan and Bugisan is closely related to the history and the role of Daeng and Bugis troops in the Keraton Yogyakarta. In Javanese language, adding the ending /-an/ can follow a noun. Daengan comes the noun “Daeng” followed by/-an/.The same is true with Bugisan which comes from the noun “Bugis” followed by /-an/.This paper discusses the history of the kampongs Daengan and Bugisan. It is expected that this paper may become a historical reference for the younger generation and the society in general.